Barley Phenolamides Effectively Scavenge Harmful Methylglyoxal In Vitro and in Mice. Issue 8 (11th March 2023) - Wang, Weixin; Zhu, Yingdong; Sang, Shengmin
Abstract : Scope: Methylglyoxal (MGO), a harmful reactive dicarbonyl, is involved in the pathogenesis and development of diabetes and diabetic complications. The goal of this study is to determine whether bioactive phenolamides in barley, p ‐coumaroylagmatine (pCAA) and feruloylagmatine (FAA), which share a similar guanidine group to diabetic drug metformin, have the capacity to detoxify MGO. Methods and results: In this study, the MGO‐trapping abilities of these two phenolamides both in vitro and in mice are evaluated. It is found that in vitro anti‐MGO capacities of pCAA and FAA are comparable to that of metformin, and both phenolamides could rapidly scavenge MGO via forming mono‐ and di‐MGO adducts validated by in‐house synthesized standards and interpretation of respective LC‐MS n ( n  = 2–3) data. Furthermore, mono‐MGO conjugates of phenolamides are detected from feces and urine of mice after oral administration of the corresponding phenolamides. Conclusion: These findings suggest that barley phenolamides may have the potentials to be developed as alternative therapeutics to prevent the development of MGO‐associated diabetes and diabetic complications. Abstract : In vitro incubation of barley phenolamides, p ‐coumaroylagmatine (pCAA) and feruloylagmatine (FAA), with methylglyoxal (MGO) demonstrates that pCAA and FAA could effectively trap MGO via formation of various mono‐ and di‐MGO adducts and their anti‐MGO capacities are comparable to known diabetic drug metformin. Further mouse study proves that ingested pCAA and FAA are able to scavenge endogenous MGO in vivo.